Al-Dawlah wa al-Da‘wah al-Islāmīyah fī ‘Ahd al-Niẓām al-Jadīd: Dirāsah fī Fikr Soeharto min Khilāl al-Khiṭābāt al-Ri’āsīyah fī al-Munāsabāt al-Islāmīyah bi Indonesia - Salam, M. Isa H.A. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2016)
This article examines the speeches by Soeharto, the second Indonesian President (1966-1998), in regard with Islamic da‘wah (preaching) in Indonesia. On various occasions of Islamic festivals such as in celebrating Mawlid al-Nabī, Isrā’ Mi‘rāj, and Nuzūl al-Qur’ān, Soeharto elucidates his main concern of the nature of da‘wah. Amid his strict opposition to political Islam, his attention to da‘wah is worth discussing. For Soeharto, religion serves as a true life-guidance that functions as the spiritual, ethical and moral basis of the statehood in Indonesia. Soeharto believes that a good da‘wah will bring a better Muslim community in Indonesia. He, therefore, warns that Muslim leaders and da‘is should not perform da‘wah by provoking conflict not only between Islam and the state, but also between Muslim community with other existing religious communities, and he often remind them that da‘wah in Indonesia should not contradict with the state ideology (Pancasila).DOI: 10.15408/sdi.v23i1.3168